2022
DOI: 10.1136/bmjopen-2021-059577
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic impact on patients with advanced non-COVID-19 illness and their family carers receiving specialised palliative home care: a qualitative study

Abstract: ObjectivesTo investigate the experiential impact of the COVID-19 pandemic on patients with non-COVID, life-threatening disease and their family carers.DesignAn interpretative qualitative design informed by phenomenological hermeneutics and based on data from in-depth interviews, performed between June and September 2020.SettingPatients receiving specialised palliative home care and their family carers living in Sweden.Participants22 patients (male/female 11/11) and 17 carers (male/female 5/12) aged 50 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Several patients have reported decreased quality of life and depression because of the COVID‐19 epidemic (Beltran‐Aroca et al, 2021; Dhavale et al, 2020; Mishra et al, 2022; Nyblom et al, 2022; Yennurajalingam et al, 2022; Yildiz Kabak et al, 2021). This change may be related to fear of infection with COVID‐19 (Mishra et al, 2022), fear of disease progression (Yildiz Kabak et al, 2021), and fear of incomplete treatment (Dhavale et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several patients have reported decreased quality of life and depression because of the COVID‐19 epidemic (Beltran‐Aroca et al, 2021; Dhavale et al, 2020; Mishra et al, 2022; Nyblom et al, 2022; Yennurajalingam et al, 2022; Yildiz Kabak et al, 2021). This change may be related to fear of infection with COVID‐19 (Mishra et al, 2022), fear of disease progression (Yildiz Kabak et al, 2021), and fear of incomplete treatment (Dhavale et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have pointed out the increased psychological burden of providing palliative care at special times (de Azeredo Siqueira et al, 2021; Dhavale et al, 2020; Franchini et al, 2021; Santin et al, 2022; Varani et al, 2021). The stress faced by caregivers stems from fear of making mistakes (Dhavale et al, 2020; Franchini et al, 2021), deterioration of their own physical health (Dhavale et al, 2020; Santin et al, 2022), additional tasks, limited support (Santin et al, 2022), fear of contracting COVID‐19 (Nyblom et al, 2022; Santin et al, 2022), the creation of social distance, and financial stress (Santin et al, 2022). One study showed that medical workers have higher rates of psychological morbidity and are more prone to burnout than before (Varani et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients and carers did, however, not think their contact with the specialised palliative care service was reduced and they valued the contact highly. 18 Danish caregivers of patients in specialised palliative homecare also expressed the fear of themselves or other would pass on COVID-19 to the patient and how it was difficult to get the most out of life due to COVID-19 restrictions. During some period of the pandemic they, also, expressed the frustration of not being able to visit the patient in the hospital and having less physical contact with the palliative home care service.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The reasons for this shift appear manifold: Foremost, PC patients themselves did not want to be admitted because they were afraid of catching the infection. Furthermore, they wanted to stay close to the people who were important to them [56,58]. An overall reduction in referrals to hospitals from primary care was observed, as they appear to have been carried out only in particularly complex clinical cases [28,58].…”
Section: Disruption Of the System Underutilization And Shift From Hos...mentioning
confidence: 99%